A long-period (P = 61.8 d) M5V dwarf eclipsing a Sun-like star from TESS and NGTS. Issue 3 (13th May 2020) - Gill, Samuel; Cooke, Benjamin F; Bayliss, Daniel; Nielsen, Louise D; Lendl, Monika; Wheatley, Peter J; Anderson, David R; Moyano, Maximiliano; Bryant, Edward M; Acton, Jack S; Belardi, Claudia; Bouchy, François; et al.
ABSTRACT: The Transiting Exoplanet Survey Satellite has produced a large number of single-transit event candidates which are being monitored by the Next Generation Transit Survey ( NGTS ). We observed a second epoch for the TIC-231005575 system ( T mag = 12.06 and T_eff = 5500 ± 85 K ) with NGTS and a third epoch with Las Cumbres Observatory's telescope in South Africa to constrain the orbital period (P = 61.777 d ). Subsequent radial velocity measurements with CORALIE revealed the transiting object has a mass of M 2 = 0.128 ± 0.003 M⊙, indicating the system is a G-M binary. The radius of the secondary is R 2 = 0.154 ± 0.008 R⊙ and is consistent with mesa models of stellar evolution to better than 1σ.